Perbedaan Berbagai Konsentrasi Ekstrak Etanol 70% Daun Belimbing Wuluh (Averrhoa Bilimbi L.) Sebagai Bahan Obat Kumur Terhadap Hambatan Pertumbuhan Bakteri Streptococcus Sanguis In Vitro SKRIPSI - Taliningrum, Klis Kondho, drg. Mahmud Kholifa, MDSc, drg. Nilasary Rochmanita S, MDSc (2014)
Plaque is a soft deposit which is firmly attached to the tooth surface consists of colonies of microorganisms that multiply, one of which is the bacterium Streptococcus sanguis. Plaque that is not treated will cause sustained disease and gingivitis to periodontitis. To prevent this, many research on the antibacterial ingredient. Starfruit leaf extract, one of herbal antibacterial ingredients that are believed to inhibit the growth of bacteria such as Streptococcus sanguis. Antibacterial power was obtained from the leaves of belimbing wuluh active substance including flavonoids, tannins, and saponins. This experimental laboratory study treatment was divided into 7 groups: 2.5%, 5%, 10%, 20%, 40% concentration of leaf extract starfruit, sterile aquades (k-), chlorhexidine 0.2% (k +) and in replication as much as 3 times. Research used the media petri dish with pitting and incubation method with 37˚C temperature for 24 hours. Clear zone which seen around the wells was then measured using a caliper with millimeters. Data was calculated using one-way ANOVA test followed by Post hoc LSD test. The results of data processing was 0,01 (p <0.05).